The Effectiveness Of Pregnant Exercise In Squat Position With Perineal Rupture In Maternity Mothers At TPMB Siti Salmah In 2022 - Salmah, Siti; Nursitiyaroh, Nursitiyaroh; Ermanto, Budi (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background : In the majority of first-time births, perineal tears last for some time. Unexpected tension that occurs in the head or body of the hatchlings causes tears in the skin and perineal tissue Writing Purpose: to determine the Effectiveness of Pregnant Squat Exercise with Perineal Rupture in Maternity Mothers at TPMB Siti Salmah Year 2022 Research Methods: this type of quantitative research uses an experimental design (quasi-experimental) ) with the Nonrandomized Control Group Pretest Posttest Design. The total population of this study was 30 mothers giving birth at TPMB Sti Salmah divided into 15 intervention groups and 15 control groups. Research Results: The results of the independent sample test obtained Asymp. Sig (2 – Sided) has a value of 0.001, because 0.001 <0.05, the hypothesis is accepted. This means that there is a difference between doing pregnancy exercise in the squat position and not doing pregnancy exercise in the squat position on the incidence of perineal rupture in pregnant women so that it can be concluded that there is effectiveness of pregnancy exercise in the squat position with perineal rupture in maternity mothers at TPMB Siti Salmah in 2022 Conclusions and Suggestions: Expected results this research allows midwives to do pregnancy exercises in a squatting position. This research will also serve as a guide for its implementation, making it easier for patients, especially pregnant women, to prepare for delivery to prevent perineal rupture.